2020
DOI: 10.3844/sgamrsp.2020.69.81
|View full text |Cite
|
Sign up to set email alerts
|

Time-Temperature Dependency of Laminated Glass Subjected to Blast Load – A Numerical Study

Abstract: The behavior of laminated glass has strong time-temperature dependency. Viscoelastic material models are often employed to define mechanical properties of Polyvinyl Butyral (PVB), the most common interlayer for structural glass applications. However, it is an apparent notion to simplify the high complexity of such material models, as only specific software is capable of considering this behavior. Most studies in blast design of laminated glass have focused on room temperature condition and recommend the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…This is essentially the speed of the car at moment of launch. Bradt (2011) ;Förch, (2020), have shown that the loading rate has an effect on glass strength, the high strain rates at impact should make the glass stronger. However small fast hard body impact on glass is much more complicated due to the induced Hertzian cone fractures, (Chaudhri 1989;2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is essentially the speed of the car at moment of launch. Bradt (2011) ;Förch, (2020), have shown that the loading rate has an effect on glass strength, the high strain rates at impact should make the glass stronger. However small fast hard body impact on glass is much more complicated due to the induced Hertzian cone fractures, (Chaudhri 1989;2015).…”
Section: Introductionmentioning
confidence: 99%